Zakai sebagai hukum Diyani Dan Qadai dan upaya Pembaruan Hukum Islam di Indonesi - Miftah, A A (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
This research will answer thefollowing problems. The first, what is meant by the diyani and qadai lqw? The second, what arguments are hold to explain zakat as diyani and qadai law? The third. Does the Act of Zakat Number 39 Year I999 indicate zakat as diyani and qadai law? Thefourth what is the zakatforms os diyani and qadai lcw in Indonesia? The fifth, does performing zakat as diyani and adai in Indonesia context have strong yuridical argument? All the problems above hence will be solvedby understanding the diyani and qadai theory as theoritical base to studi zakat. Afterward, theÂ  xamination of the theory will be directed to the zakat concept in Islamic religion. Studying the zakat concept will benefit to be used as a Jramework in studying zakat in the act of zakat number 38 year 1999. The act will widely be analized, not only its content but also its socio-historical context.The analysis toward this act aims at understanding and making sure that zakat as merely diyani and qadai law at once. There are some arguments to say that zakat as diyani and qadai law,from the view of its definition, law base, implementation, similary and dffirence with taxtation, and the position of zakat wealth for muzakki and mustahiq. The act of zakat number 38, 1999 already exisls bul zakat in the act doesnt reflect zakat as diyani and qadai totally. There are some arguments to implement zakat as diyani and qaclai law in Indonesia: historical, philoshopical, sociological, as well as yuridical, aplication of the law, and the